2011
DOI: 10.1001/archneurol.2011.68
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cerebral Vasoconstriction Syndromes

Abstract: Objectives: To compare the clinical, laboratory, and imaging features of patients with reversible cerebral vasoconstriction syndromes evaluated at 2 academic centers, compare subgroups, and investigate treatment effects. Design: Retrospective analysis. Setting: Massachusetts General Hospital (n = 84) or Cleveland Clinic (n = 55). Patients: One hundred thirty-nine patients with reversible cerebral vasoconstriction syndromes. Main Outcome Measures: Clinical, laboratory, and imaging features; treatment; and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
624
8
48

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 557 publications
(705 citation statements)
references
References 30 publications
25
624
8
48
Order By: Relevance
“…In a previous study, we found no major differences in RCVS subgroups defined by risk factors and triggers. 4 These data suggest that the phenotype of RCVS is relatively homogenous regardless of lesion type or precipitant.…”
Section: Strokementioning
confidence: 82%
See 4 more Smart Citations
“…In a previous study, we found no major differences in RCVS subgroups defined by risk factors and triggers. 4 These data suggest that the phenotype of RCVS is relatively homogenous regardless of lesion type or precipitant.…”
Section: Strokementioning
confidence: 82%
“…The clinical and brain-imaging features of the first 159 patients have been published. 1,4 We were careful to exclude patients with primary angiitis of the central nervous system, a close mimic of RCVS, based on published criteria. 1 Serial cerebral angiography confirmed reversibility in 128 patients, and 30 patients developed sudden, severe headaches, segmental arterial narrowing on cerebral angiography, and had a self-limited clinical course in the absence of immunosuppressive treatment and no recurrences during follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations